Submicron Polymer Emulsion Inside Twin Screw Extruder - Arefi, Ahmad (My University, 2023)
Solvent-free extrusion emulsification (SFEE) is a recently developed process for producing submicron particles with high viscosity polymers inside a twin-screw extruder without the use of hazardous solvents. Its dependency on a catastrophic phase inversion makes the process knowingly sensitive to a variety of formulation and operational variables, causing a narrow window of production. The purpose of this thesis was to investigate and improve process stability as well as widening operational window. Transient effects of the start-up procedure was investigated by considering the process stability and particle size distribution. The transient sensitivity corresponded to the residency of material in the dispersion zone. When a sub-optimal water/surfactant fraction was allowed to produce an undesired polymer-water (thick lamella) morphology, this morphology continued to persist until the critical first half of the dispersion zone was purged of existing mass. Lot to lot variability of polyester resin was used to investigate the sensitivities of the SFEE process more deeply to better understand the mechanism involved. In this case, acid number was shown to have a significant effect on the initial amount of water needed in the dispersion zone for phase inversion, resulting in an emulsification boundary dependent on the resin acid number. In fact, a significant correlation was found between the acidic end groups of the resin and the maximum amount of water content that could be used in the dispersion zone. The effect of feed rate, screw speed, dispersion length, and surfactant concentration were studied for their individual influence on widening the emulsification boundary. The most significant improvement was observed by applying a longer dispersion length or lower feed rate because both significantly increase the residence time. The effect of residence time on the emulsification boundary was attributed to the total strain imposed on the polymer/water mixture which was related to interfacial growth in the dispersion zone.
Keywords: Emulsion Emulsification; Polymer Dispersion; Twin Screw Extruder; Catastrophic Phase Inversion; Submicron/Nano Particles; Solven-Free Extrusion Emulsification; Scale-up; Dynamic Phase Inversion